Pharmacokinetics, pharmacodynamics, safety, and immunogenicity of HLX14 versus reference denosumab in healthy males: A randomized phase I study - Nanyang Li; Nannan Chu; Leilei Zhu; Xiaojie Wu; Qiong Wei; Jiahui Wang; Xuhui Hu; Haoyu Yu; Qingyu Wang; Wei'an Yuan; Kai Huang; Jing Zhang (Clinical and Translational Science)
Abstract Denosumab is a human IgG2 monoclonal antibody against receptor activator of nuclear factor kappa‐B ligand (RANKL) for the treatment of osteoporosis and bone loss. HLX14 is a proposed biosimilar of denosumab. This randomized, parallel‐group, two‐part, phase I study aimed to compare the pharmacokinetics, pharmacodynamics, safety, and immunogenicity of HLX14 with reference denosumab in Chinese healthy adult male participants. In Part 1, participants were randomized 1:1 and given HLX14 or reference denosumab sourced from the European Union (EU). In double‐blind Part 2, participants were randomized 1:1:1:1 to receive HLX14 or denosumab sourced from the United States, EU, or China. All study drugs were administered via subcutaneous injection at a single dose of 60 mg. The primary endpoints were area under the serum drug concentration–time curve from time 0 to the last concentration‐quantifiable time t (AUC0–t), maximum serum drug concentration (Cmax), and area under the serum drug concentration–time curve from time 0 to infinity (AUC0–inf). Twenty‐four participants were randomized in Part 1 and 228 in Part 2. The 90% confidence intervals of geometric mean ratio of AUC0–t, Cmax, and AUC0–inf between HLX14 and denosumab from different sources fell within the pre‐specified similarity margins of 0.80–1.25 (AUC0–t, 0.91–1.13; Cmax, 0.91–1.13; AUC0–inf, 0.91–1.12), demonstrating pharmacokinetic similarity. No notable difference was observed among treatment groups in pharmacodynamics, safety, or immunogenicity. HLX14 demonstrated highly similar pharmacokinetic characteristics with comparable pharmacodynamics, safety, and immunogenicity to denosumab, supporting its further investigation as a potential denosumab biosimilar.